An evaluation on meaning of bahasa Indonesia dubbing found in Spongebob Squarepants cartoon based on linguistic, cultural, and children’s literature aspects - Yuni Savitri Maulani; Sufriati Tanjung (LingTera, 2017)
This research is in the scope of the translation evaluation of Spongebob Squarepants based on linguistic, culture and children literature aspects. This study aimed to evaluate: (1) Both of appropriate and inappropriate meaning based on linguistic aspects  which consist of: grammatical hierarchy and translation type in Spongebob Squarepants dubbing, (2) The meaning leads to the gay and capitalism cultural aspects in Spongebob Squarepants dubbing, and (3) The unlogic meaning to children's literature aspect in Spongebob Squarepants dubbing.This research is a descriptive-qualitative method, with the subject is Bahasa Indonesia dubbing's Spongebob Squarepants while the object is meaning evaluation on linguistic, cultural and children literature. The data analysis uses Milles and Hubberman (1992) The research results are: (1) Based on linguistic aspect is taken from 7 dialogues of Spongebob Squarepants Bahasa Indonesia dubbing of Newmark's, the meaning has been good overall, because they no inappropriateness or translation error in word, phrase, clause and sentence. which is a lot of inappropriate meaning so that it causes a total error meaning (neither semantic sentence nor communicative), (2) The cultural aspect related to gay and capitalism cultural taken from  dialogues of Spongebob Squarepants Bahasa Indonesiadubbing, in accordance with one of Newmark's criterion that is the culture uses target language culture. Later, the most dominant of gay cultural are in episodes 5 and 6, example: Sandy: A Citylacra SpongeBob: Sandy, please..the language! While capitalism is in episodes 1 and 3, example: We're getting a goermet chef from the chef exchange program and I'm going to raise me price to the roof, and (3) Based on children's literature aspect taken from dialogues of Spongebob Squarepants which are not related to its elements in accordance with Kennedy's criterion mostly about: the sea world theme as if land world, illogic sea creatures such as: a sponge, a computer,, and a squirrel, and also the setting about American terms applied in seabed.